DIVERSITY OF ANTIBACTERIAL COMPOUNDS FROM EUCHEUMA SERRA, HALIMEDA OPUNTIA, AND HYDROCLATHRUS CLATHRATUS - Anggadiredja, Jana Tjahjana (Jurnal Teknologi Lingkungan, 2011)
Fourteen compounds were isolated from acetone extracts of three species of seaweeds (Eucheuma serra, a red seaweed, Halimeda opuntia, a green seaweed, and Hydroclathrus clathratus, a brown seaweed) using bioautographic TLC methods and identified using GC-MS. From Eucheuma serra were isolated 8 compounds (3 fatty acids, 3 steroids, and 2 aldehyds). Only two compounds of fatty acid camefrom Halimeda opuntia, whereas Hydroclathrus clathratus produced 6 compounds (4 fatty acids, one compound each of steroid and ether). All isolated single compoundswere tested for their antibacterial activities by the agar diffusion method against the Gram-positive bacteria Staphylococcus aureus, Bacillus subtilis and Streptococcusfaecalis, and the Gram-negative bacteria Echerichia coli, Pseudomonas aeruginosa and Salmonella typhimurium. All 14 compounds showed activity against Gram-positivebacteria, especially Bacillus subtilis, and only 2 compounds showed activity against Gram-negative bacteria Escherichia coli. Nine compounds showed activity against Staphylococcus aureus, and 4 compounds showed activity against Streptococcusfaecalis. All compounds were not active against Pseudomonas aeruginosa andSalmonella typhimurium bacteria. This study indicated that there is indeed a diversityboth in kinds and in molecular structures of the antibacterial substances.